2023
DOI: 10.1088/1674-1056/aca205
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and controllable reflected group delay based on Tamm surface plasmons with Dirac semimetals

Abstract: In this paper, the reflected group delay from a multilayer structure where bulk Dirac semimetals (BDS) is coated on one-dimensional photonic crystal (1D PC) separated by a spacer layer is investigated theoretically. It is shown that the group delay of reflected beam in this structure can be significant enhanced negatively and can be switched from negative to positive. The enhanced group delay originates from the steep phase change caused by the excitation of optical Tamm state (OTS) at the interface between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…They have proved that dynamic tuning of the group delay value can be achieved by varying the Fermi energy of the BDS via an external voltage. 22 Jiang et al have designed a perfect absorber based on BDS metamaterials and realized tunable absorption by applying a bias voltage to change the Fermi energy of the BDS. 23 In addition, the BDS also has other superior physical properties to monolayer graphene, including a lower plasmonic loss, better structural stability and easier processing.…”
Section: Introductionmentioning
confidence: 99%
“…They have proved that dynamic tuning of the group delay value can be achieved by varying the Fermi energy of the BDS via an external voltage. 22 Jiang et al have designed a perfect absorber based on BDS metamaterials and realized tunable absorption by applying a bias voltage to change the Fermi energy of the BDS. 23 In addition, the BDS also has other superior physical properties to monolayer graphene, including a lower plasmonic loss, better structural stability and easier processing.…”
Section: Introductionmentioning
confidence: 99%
“…In atomic systems, EIT is a quantum interference phenomenon between two excitation pathways [11]. Researchers have been actively studying the optical analog of EIT and EIR in various photonic crystals [12] and photonic metamaterials [13][14][15]. Recently, Shen et al reported an all-optical analog to electromagnetically induced transparency based on higher-order topological states [16].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al investigated optical Tamm states in hetero-structures with highly dispersive planar plasmonic metamaterials to show the EIR-like effect. In the search for new plasmonic materials, bulk Dirac semimetals (BDS) are becoming more significant due to their ultrahigh carrier mobility and tunable conductivity [15,[22][23][24]. The control over Fermi energy and relative permittivity make it a suitable plasmonic material for photonic applications [25].…”
Section: Introductionmentioning
confidence: 99%